Hermeneutika Al-Qur’an: Antara Pemaknaan Tekstual dan Kontekstual - Slamet Muliono R (Ulumuna, 2010)
This article aims to describe the basic philosophy of the hermeneutics view about how to interpret al-Qur’an using the modern science. In the modern life, we find many problem which has not happened in the past. Tafsir method is supposed not to be able to solve the social problems which should be looked for an immediate solution while the social problems are so much. Hermeneutics supposed that by using hermeneutics, we can interpret al-Qur’an according to the modern challenges which could not be invented in the early of Islam. Hermeneutics method has been acknowledged as a new vision about Islam. But hermeneutic view, if we are not careful, could destroy the basic values of Islam which has participated for the Islamic civilization. The negative effects of hermeneutic method are, deconstructing writings of the ‘ulama, infiltration of West values, absolute value of Islamic will be lost, and making al-Qur’an as human product.